Trading efficiency of fund families: Impact on fund performance and investment behavior - Gjergji Cici; Laura K. Dahm; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2014)
Mutual funds are part of larger organizations, which make decisions with consequences for all their member funds. This study examines how the efficiency of trading desks operated by fund families affects the performance and trading of affiliated funds. We introduce a novel approach to measure the efficiency of trading desks, which allows for comparisons across families with different investable universes. By operating efficient trading desks, which reduce trading costs, fund families improve the performance of their funds significantly. Furthermore, the lower trading costs resulting from more efficient trading desks enable mutual funds to trade more and hold less liquid portfolios.
Keywords: D23; G23; G24; 330; mutual funds; fund families; trading efficiency; fund performance; investment behavior